Perfusion Index and its association with hypotension following spinal anaesthesia for lower segment caesarean section in a tertiary care center of rural Nepal - Khapung, Robin; Basnyat, Subi; Singh, Rohit Man; Silwal, Shirish; Thapa, Anita; Pandey, Alan; Adhikari, Apil; Giri, Praveen Kumar; Bhattarai, Ramesh; Limbu, Posan Samser; et al. (Journal of Karnali Academy of Health Sciences, 2025)
Introduction: Spinal anaesthesia is the preferred technique for lower segment caesarean section (LSCS) but is frequently complicated by hypotension. Conventional monitoring may not detect hypotension early, prompting interest in non-invasive predictors such as the perfusion index (PI). This study aims to evaluate the utility of baseline PI as an early predictor of spinal anaesthesia-induced hypotension in parturients undergoing LSCS at a tertiary care centre in rural Nepal. Methods: This prospective observational study was conducted at Karnali Academy of Health Sciences from September 2024 to August 2025 after ethical approval. Parturients aged 18–40 years (ASA I–II) undergoing elective LSCS under spinal anaesthesia were enrolled. Haemodynamic parameters were recorded. Data were analyzed using SPSS v20 with p < 0.05 considered significant. Results: A total of 86 parturients were enrolled with a median age of 27 years and gestational age of 41 weeks. Post-spinal hypotension occurred in 27 (31.4%) patients, with 31 (36%) requiring mephentermine support; bradycardia (3.5%) and vomiting (2.3%) were minor adverse events. Baseline perfusion index showed a significant association with post-spinal hypotension (p < 0.001) and a negative moderate correlation with mean arterial pressure (r = –0.373, p < 0.001) and systolic blood pressure (r = –0.368, p = 0.001), while no association was observed with parity or caesarean history. Conclusion: Baseline PI >3.5 predicts spinal-induced hypotension in elective CS, with higher incidence, lower early MAP, and negative PI-MAP correlation. It may be used for early risk identification and haemodynamic management.